Renwick, Roger deV. Recentering Anglo-American Folksong: Sea Crabs and Wicked Youths. Jackson: UP of Mississippi, 2001.183 pp. - C. Rouse, Andrew (FOCUS: Papers in English Literary and Cultural Studies, 2002)
In the “Introduction” to this long-awaited volume, Roger Renwick provides us with what might be described as a definitive list of the important collectors and scholars of Anglo/American folk songs, beginning with D. K. Wilgus, whose “intellectual history of Anglo-American Folksong Scholarship Since 1898” was published in 1959, and continuing with Bronson, Coffin and Laws, all of them followers of the great nineteenth-century collector of Harvard University Francis James Child. Renwick’s own book is not intended to follow suit with these names, all of them so familiar to the ballad scholar, but rather to examine why the study of folksong has lost the influence it once had, and why “increasingly it seems that the same fate may very well be in store for the supra-discipline, folklore itself".